Early adopters of 6-month levofloxacin as rifampicin-resistant tuberculosis preventive treatment regimen in the WHO European Region, 2023 - Andrei Dadu (Eurosurveillance)
Tuberculosis (TB) preventive treatment (TPT) is crucial for preventing infection with Mycobacterium tuberculosis from progressing to TB disease, especially among people in high-risk groups. The expansion of novel TPT regimens for drug-susceptible TB is a notable advancement in TB care. However, managing contacts of drug-resistant TB patients remains a major challenge, particularly in Eastern Europe and Central Asia. In 2020, the World Health Organization (WHO) recommended TPT for high-risk household contacts of multidrug-resistant (MDR) or rifampicin-resistant (RR) TB patients; this was further reinforced in 2024 with a recommendation of a 6-month levofloxacin (6-Lfx) regimen. This Perspective discusses the early adoption of 6-Lfx for MDR/RR-TPT in the WHO European Region. In 2023, 38 of 53 WHO European Region countries reported on 6-Lfx use, with only eight confirming its use for MDR-TB contact persons. Accelerating the adoption of the 6-Lfx regimen and other evidence-backed TPT regimens is crucial for achieving TB elimination in the WHO European Region. Addressing challenges such as slow uptake of the recommendations, low awareness in affected communities and resource shortages are essential for success.